"Science" and Spiritual Vibrations: Contemporary Spiritualism and the Discourse of Science - Porter, Jennifer (My University, 1995)
Spiritualism is a religious movement based on communication with the spirits of the dead that originated in New York State in 1848. From its inception, members of the movement claimed that communication with the spirits of the dead was not only a possibility, but was in fact "scientifically" verifiable. Attempts were made throughout the nineteenth century to establish the "truth" of Spiritualist claims to scientific legitimacy. Although there are no longer any overt connections between Spiritualism and the scientific establishment, contemporary Spiritualists continue to insist that their beliefs are in accord with "science." Drawing upon fieldwork with contemporary Spiritualists in Hamilton, Ontario and Lily Dale, New York, this dissertation argues that scientific language and symbols have been incorporated into contemporary Spiritualist discourse to articulate and legitimate the claim that Spiritualist experiences are "true" in a "scientific," empirical sense. An examination of Spiritualist healing, mediumship and narrative practice reveals the extent to which the discourse of "science" has become the means by which the "reality" and "truth" of Spiritualist beliefs are affirmed. In articulating the "truth" of Spiritualist experience and the "reality" of the spirit hypothesis, the language and symbols of science are transformed into a sacred discourse that at once legitimates and affirms Spiritualist beliefs while simultaneously criticizing the "narrow" limits of orthodox science. For many contemporary Spiritualists, "science" has become the language in which religious truth claims are expressed.
Keywords: Spiritual Vibrations; Discourse of Science